2009
DOI: 10.1007/s11518-009-5120-3
|View full text |Cite
|
Sign up to set email alerts
|

A DEA-TOPSIS method for multiple criteria decision analysis in emergency management

Abstract: A hybrid approach of DEA (data envelopment analysis) and TOPSIS (technique for order performance (preference) by similarity to ideal solution) is proposed for multiple criteria decision analysis in emergency management. Two DEA-based optimization models are constructed to facilitate identifying parameter information regarding criterion weights and quantifying qualitative criteria in TOPSIS. An emergency management case study utilizing data from the Emergency Management Australia (EMA) Disasters Database is pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 35 publications
(24 reference statements)
0
19
0
Order By: Relevance
“…More recent literature has also shown that decision outcomes can be strengthened by merging the application of DEA with other quantitative approaches such as Artificial Neural Networks [39], the Knapsack problem [36], Analytical Hierarchy Process [34], Analytic Network Process [38], TOPSIS [42,43], and fuzzy logic [34,36].…”
Section: Literature Reviewmentioning
confidence: 99%
“…More recent literature has also shown that decision outcomes can be strengthened by merging the application of DEA with other quantitative approaches such as Artificial Neural Networks [39], the Knapsack problem [36], Analytical Hierarchy Process [34], Analytic Network Process [38], TOPSIS [42,43], and fuzzy logic [34,36].…”
Section: Literature Reviewmentioning
confidence: 99%
“…This numerical example is re-analyzed using the new method, and the results compared with those from VIKOR and TOPSIS. An additional case study, using data from the Emergency Management Australia (EMA) Disasters Database, is presented in [32]. It is based on a refined version of this method, and is recommended as another practical application.…”
Section: Comparative Studiesmentioning
confidence: 99%
“…Multi-criteria decision making (MCDM) methods have therefore been extensively employed to study emergency management, for instance, the Ordered Weighted Averaging (OWA) [2], Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) [3], Preference Ranking Organization Method for Enrichment Evaluations (PROMETHEE) [4], Analytic Hierarchy Process (AHP) ( [5], [6],and [7]), Analytic Network Process (ANP) ( [8], [9]), Decision Making Trial and Evaluation Laboratory (DEMATEL) [10], Fusion Approach of MCDM (FAMCDM) methods [11] etc. Among these MCDM methods, AHP and ANP are two of the most popular methods for studying emergency management, and usually used to assess the emergency management performance, select the best emergency response alternatives or emergency recovery alternatives and allocate reasonable relief resources etc.…”
Section: Introductionmentioning
confidence: 99%